The radiation intensity of the Lyman alpha line at the ionization front in the quasi-steady plasma accelerator - Kozlov, A.N.; Garkusha, I.E.; Konovalov, V.S.; Novikov, V.G. (Вопросы атомной науки и техники, 2013)
Research of the radiation transport in the ionizing gas streams in the channel of the quasi-steady plasma accelerator is carried out. The quasi-one-dimensional model of the ionizing gas flow includes the MHD equations combined with the ionization and recombination kinetics equation within the framework of the modified diffusion approximation. Solution of the radiation transport equation is based on calculation of the plasma emissivity, the photon absorption coefficients, the line profile and use of the method of characteristics. Distribution of the radiation intensity for the Lyman alpha line is obtained, and also the integrated values of the density of the radiation energy and the radiation energy flux for all parts of the hydrogen spectrum along the accelerator channel are presented. Проведено исследование переноса излучения в потоках ионизующегося газа в канале квазистационарного плазменного ускорителя. Квазиодномерная модель течения ионизующегося газа основана на МГД- уравнениях с учетом кинетики ионизации и рекомбинации в рамках модифицированного диффузионного приближения. Моделирование переноса излучения основано на вычислении излучательной способности и коэффициента поглощения фотонов, определении профиля и использовании метода характеристик. Получено распределение интенсивности излучения центра альфа-линии Лаймана, а также распределения плотности энергии и плотности потока энергии излучения для всего спектра вдоль канала ускорителя. Проведено дослідження перенесення випромінювання в потоках газу, що іонізується, в каналі квазістаціонарного плазмового прискорювача. Квазіодновимірна модель течій гaзу, що іонізується, заснована на МГД-рівненнях з урахуванням кінетики іонізації і рекомбінації в рамках модифікованого дифузійного наближення. Моделювання перенесення випромінювання засноване на обчисленні випромінювальної здатності і коефіцієнтa поглинання фотонів, визначенні профілю і використанні методу характеристик. Отримано розподіл інтенсивності випромінювання центрa альфа-лінії Лаймана, а також розподіли густини енергії і густини потоку енергії випромінювання для всього спектрa уздовж каналу прискорювача.